A recommendation system for teaching strategies according to learning styles - Figueroa-Pérez, Juan Francisco; Rodríguez-Guerrero, Manuel; Ramírez-Noriega, Alan; Martínez-Ramírez, Yobani (Institute of Advanced Engineering and Science, 2025)
Teaching strategies (TS) are resources, procedures, techniques, and/or methods that teachers use as instruments to promote meaningful learning in students and that have proven to be efficient as support in classroom teaching. This paper describes a recommendation system (RS) for teaching strategies according to learning styles (RSTSLS) that helps to determine the most appropriate TS to use according to the learning style (LS) of the students based on Felder and Silverman’s learning styles model (FSLSM). A working example of the system is provided, as well as the results of its functional and non-functional tests, which were satisfactory. It is concluded that the system can be useful as a support tool for teachers, allowing them to adapt their TS according to the LS of their students.